Are CONSORT checklists submitted by authors adequately reflecting what information is actually reported in published papers? - Blanco, D; Biggane, A; Cobo, E; Altman, D; Bertizzolo, L; Boutron, I; Gkioni, E; Glonti, K; Kirkham, J; Olarte, C; Olsen, M; Superchi, C (BioMed Central, 2018)
Background Compulsory submission of a checklist from the relevant reporting guideline is one of the most widespread journal requirements aiming to improve completeness of reporting. However, the current suboptimal levels of adherence to reporting guidelines observed in the literature may indicate that this journal policy is not having a significant effect. Findings We explored whether authors provided the appropriate CONSORT checklist extension for their study and whether there were inconsistencies between what authors claimed on the submitted checklist and what was actually reported in the published paper. We randomly selected 12 randomized trials from three journals that provide the originally submitted checklist and analyzed six core CONSORT items. Only one paper used the appropriate checklist extension and had no inconsistencies between what was claimed in the submitted checklist and what was reported in the published paper. Conclusion Journals should take further actions to take full advantage of the requirement for the submission of fulfilled CONSORT checklists, thus ensuring that these checklists reflect what is reported in the manuscript.